The Use Malays-Sambas Expressions in Developing Character Education in Sambas Primary Madrasah in Millennial Era - Putra, Purniadi; Kartika MR, Galuh Nashrulloh; Hafiz, Abdul; Pratama, Dendi; Samad, Abdul (Jurnal Ilmiah Peuradeun, 2021)
The Malays-Sambas expression is believed to have contributed to the Islamic basic education through an emphasis on a culture of shame expression that reflects the honor, reputation, and self-esteem of foreign cultures. The purpose of this study was to analyze the expression of Malay Sambas in improving the character education of Islamic primary students. The naturalistic phenomenological method was used to analyze the data of 6 students, 3 principals, and classroom teachers through in-depth interview sessions. The voices of participants with homogeneous characteristics of the Sambas Malay ethnicity were recorded and analyzed looking at the characteristics and implications, among others: 1) Exploration of the Sambas Malay; Suppan said, "a small wrong hand is set up" means respect, openness, gentle words, and the expression of the language of "tullah"(damned) to teach children, should not conflict with parents, teachers or parents. 2) The contribution of the Malay-Sambas language has significant character education value. Therefore, these findings contributed to schools in creating a model of local wisdom curriculum that aims to explore the richness of local values integrated into formulating the lives of a good millennial generation, so that they can maintain their values ​​while respecting globalization dominance.